Hunter-gatherer manufacture, use, and discard of blades at the northern margin of Viedma Lake (southwest of Santa Cruz, Argentina): Late Holocene differences in landscape use - Belardi, Juan Bautista; Espinosa, Silvana Laura; Carballo Marina, Flavia; De Angelis, Hernán (Arqueología, 2023)
Using a morphological, technological, and use-wear analysis approach, we study assemblages of blades and by-products of their manufacture (laminar flakes, chunks, cores, and tools) recovered on Viedma lake northern shore. The artifactual samples come from different archaeological contexts of altitudinal sectors of the steppe (Coast —wintering fields, ≤ 400 m asl—, Intermediate Pampas and Tobiano Plateau ≥ 900 m asl) related to Late Holocene chronologies. The higher frequencies of flintknapping and discard evidences, in addition to the integrity of the samples, the artifactual composition, and the high availability of basalt nodules of dimensions and qualities suitable for flintknapping, show the manufacture and immediate use of blades within the framework of expedient strategies in residential spaces of the coast. The efficiency of blades to perform cutting tasks could be linked to the processing of guanaco. Thus, the blade assemblages recovered at the coast support a substantial difference in the hunter-gatherer use of the northern shore of Viedma lake. It is proposed that the production of blades has a supraregional manifestation shared by areas of the Tar and Argentino lake coasts, located to the North and South of Viedma lake, respectively. The characteristics of the archaeological contexts with higher blade frequency would explain their use within a background provided by flake technology.